Belonging to Multiple Nationalities: A Phenomenological Study - Peters, Annette; Softas-Nall, Basilia; Martinez, Megan (Advances in Social Sciences Research Journal, 2017)
The purpose of this qualitative study was to explore the lived experiences of individuals who identify with multiple nationalities. As the world becomes increasingly global and more individuals migrate, it is becoming commonplace for individuals to identify with more than one nationality. Psychologists and mental health professionals need to be aware of the impact of having multiple nationalities integrated into one’s identity in order to gain a deeper understanding and provide more effective treatment to these individuals. A phenomenological research design was utilized in this study. Ten participants identifying with more than one nationality (age range = 25 to 46, = 30.1) were interviewed. Several themes emerged within a context of intersectionality including: (a) process of constructing a multiple nationality identity; (b) intentionality about identifying with multiple nationalities; (c) reactions of others; (d) cultural intelligence—openness, appreciation, and acceptance of diversity; (e) similarities between cultures, language, religions, and spiritualties across nationalities; (f) feeling connected or disconnected through language; (g) where is home, and where do I belong?; (h) professional identities; and (i) importance of food. Participants provided recommendations for mental health professionals. Theoretical, research, and clinical implications are discussed.